PENGARUH JUMLAH KONSUMSI TABLET FE TERHADAP KADAR HEMOGLOBIN PADA IBU HAMIL TRIMESTER III DI PUSKESMAS PURWOKERTO BARAT TAHUN 2012 - , Siti Angkati, Sumarni; , Akademi Kebidanan YLPP Purwokerto, Riyanti (Jurnal Kebidanan, 2014)
ABSTRACT Mothers mortality can happen because of several causes such as bleeding caused byanemia. One of the anemia preventions on pregnant mother is by giving Fe tablet. Health departement of Republic Indonesia decided that the giving of blood tablet is minimally 90 tablets during pregnancy with minimally 1 tablet a day after having a meal.This research aimed to know the influence between the number of Fe tablet consumption with Hemoglobin degree on pregnant mother trimester III in Purwokerto Barat Health Center in 2012. This studyis an observational research with cross sectional approach and a way of sampling using total sampling technique with a sample of 54 respondents. The data analysis using simple line a rregression test. The result : 1) Characteristics of respondents: education high school average of 38 people (70.37%), aged 20-35 years 44 people (81.48%), occupation housewife 46 people (85.19%), gestational age of 8 months 25 people (46.30%), parity multigravida 29 people (53.70%), 2) Number of Fe tablet consumption on average as many as 107 tablets, 3) the average hemoglobin level was 9.83 g%, 4) there is the influence of the amount of Fe tablet consumption on levels of hemoglobin in third trimester pregnant women in Purwokerto Barat health center with a correlation value R2 of 81.4%. There is influence between the number of Fe tablet consumption with Hemoglobin degree on pregnant mothers trimester III inhealth centersof Purwokerto Baratin 2012.The need topay attention totheconsumption ofFetabletsduringpregnancyto preventanemiainpregnancy. Â  Keywords : the numbers of Fe tablet consumption with Hemoglobin degree